Neutral Ceramidase Is Required for the Reproduction of Brown Planthopper, Nilaparvata lugens (Stål) - Shi, Xiao-Xiao; Zhu, Mu-Fei; Wang, Ni; Huang, Yuan-Jie; Zhang, Min-Jing; Zhang, Chao; Ali, Soomro A.; Zhou, Wen-Wu; Zhang, Chuanxi; Mao, Cungui; Zhu, Zeng-Rong (Frontiers in Physiology, 2021)
Ceramides are bioactive sphingolipids that have been implicated in insect development; however, their role in insect reproduction remains poorly understood. Here we report a pivotal role of neutral ceramidase (NCER) in the female reproduction of brown planthopper (BPH), Nilaparvata lugens (Stål), a significant pest in rice cultivation in Asia. LC-MS/MS demonstrated that, among different developmental stages of BPH, the levels of ceramides were highest in the 1st instar nymphs and lowest in adults. The transcription of NCER was negatively correlated with the levels of ceramides at different developmental stages of BPH, in that the transcript levels of NCER were the highest, whereas ceramides levels were the lowest in the BPH adults. Knocking down NCER through RNA interference (RNAi) increased the levels of ceramides in BPH females and ovaries, which resulted in a delay in oocyte maturation, a reduction in oviposition and egg hatching rate, as well as the production of vulnerable offspring. Transmission electron microscopic (TEM) analysis and TdT-mediated dUTP Nick-End Labeling (TUNEL) assays showed the mitochondrial deficiency and apoptosis in NCER-deficient oocytes. Taken together, these results suggest that NCER plays a crucial role in female reproduction in BPH, likely by regulating the levels of ceramides.